Screening for Cryptococcal Antigenaemia in Patients Accessing an Antiretroviral Treatment Program in South Africa - Jarvis, Joseph N (2009)
BACKGROUND: Cryptococcal meningitis is a leading cause of death in AIDS patients and contributes substantially to the high early mortality in antiretroviral treatment (ART) programs in low-resource settings. Screening for cryptococcal antigen (CRAG) in patients enrolling in ART programs may identify those at risk of cryptococcal meningitis and permit targeted use of pre-emptive therapy. METHODS: In this retrospective study, CRAG was measured in stored plasma samples obtained from patients as they enrolled in a well characterised ART cohort in South Africa. The predictive value of screening for CRAG prior to ART for development of microbiologically confirmed cryptococcal meningitis or death during the first year of follow-up was determined. RESULTS: Of 707 participants with a baseline median CD4 count of 97 (IQR 46-157) cells/μL, 46 (7%) had a positive CRAG. Antigenaemia was 100% sensitive for predicting development of cryptococcal meningitis during the first year of ART and in multivariate analysis was an independent predictor of mortality (AHR 3.2, 95%CI 1.5-6.6). Most (92%) cases of cryptococcal meningitis developed in patients with a CD4 count ≤100 cells/μL. In this sub-set of patients, a CRAG titre ≥1 in 8 was 100% sensitive and 96% specific for predicting incident cryptococcal meningitis during the first year of ART in those with no previous history of the disease. CONCLUSIONS: CRAG screening prior to commencing ART in patients with a CD4 count ≤100 cells/μL is highly effective at identifying those at risk of cryptococcal meningitis and death and might permit implementation of a targeted pre-emptive treatment strategy.